2001
DOI: 10.1128/cdli.8.4.850-851.2001
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Involvement in Uncomplicated Herpes Zoster

Abstract: We prospectively evaluated herpes zoster patients during the acute phase of the disease for central nervous system involvement. Of 24 patients with spinal zoster, 13 (54%) had spinal cord abnormality, which was asymptomatic in 12 of the 13. Age but not lack of acyclovir treatment was associated with such involvement. In all but 2, neurological involvement resolved within 6 months. Although the mechanism responsible for the neurological abnormalities is unknown, findings may support the hypothesis that zoster i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The first possibility is that VZV migrated transaxonally or transynaptically into the brain stem parenchyma without arterial involvement. The notion that VZV migrates transaxonally to the CNS after reactivation from ganglia is supported by earlier imaging studies that demonstrated segmental spinal cord or focal brainstem abnormalities after zoster [6,7]. Transaxonal spread of virus into the CNS is also supported by the fact that our patient developed progressive neurological deficit, not transient ischemic attacks, until treatment with intravenous acyclovir was instituted.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The first possibility is that VZV migrated transaxonally or transynaptically into the brain stem parenchyma without arterial involvement. The notion that VZV migrates transaxonally to the CNS after reactivation from ganglia is supported by earlier imaging studies that demonstrated segmental spinal cord or focal brainstem abnormalities after zoster [6,7]. Transaxonal spread of virus into the CNS is also supported by the fact that our patient developed progressive neurological deficit, not transient ischemic attacks, until treatment with intravenous acyclovir was instituted.…”
Section: Discussionsupporting
confidence: 49%
“…The MRI finding of bilateral contrast enhancement in the brainstem and cerebellum corroborated evidence of CNS involvement. Previous reports have revealed MRI abnormalities on T2-weighted images of the brainstem or spinal cord in patients with acute zoster [6,7]. In these studies, only a subset of the patients with MRI abnormalities had symptoms or signs that suggested CNS dysfunction.…”
Section: Discussionmentioning
confidence: 93%
“…There was strong evidence of VZV in the CSF in 14 of 46 patients (35%), either in the form of a positive PCR or as anti-VZV antibodies. A prospective study by Steiner et al 6 to evaluate CNS involvement in the acute phase of HZ infection showed clinical evidence of spinal cord involvement (long tract signs, sensory level, pyramidal limb weakness and/or sphincter involvement) in 12 of 24 patients without any clinical symptoms. This study suggested that the mechanisms responsible for CNS involvement could be immune-mediated or infectious.…”
Section: Discussionmentioning
confidence: 99%
“…CNS complications related to ZZ infection include myelitis, aseptic meningitis, encephalitis and ventriculitis (2,4,5). Myelitis and aseptic meningitis are thought to be caused by dissemination of the virus directly into the CNS from the related nerve.…”
Section: Discussionmentioning
confidence: 99%